A STUDY ON THE ABILITY OF THE SECOND SEMESTER STUDENTS OF FKIP UNIVERSITAS RIAU ENGLISH STUDY PROGRAM IN WRITING A PARAGRAPH - Saputra, Rizky Ade; Eliwarti, Eliwarti; Erni, Erni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This descriptive research is aim to find out the ability of the second semester students of English Study Program FKIP Universitas Riau in writing a paragraph. The sample of this research is one of the three classes of the first year students of English Study Program which are choose by using cluster random sampling technique. The number of the sample is 37 students. The data were collected by giving a written test to the student individually. The test asked the students to write a paragraph by choosing one of the given topics. The students’ scores were analyzed by using Harris’ scoring system which concerned with five aspects of writing, they are Grammar, Vocabulary, Mechanics, Fluency and Organization. The findings show that the students’ average score for each aspect of writing was in “good” level where the students’ ability in terms of Vocabulary was the highest among the other aspects with the average score 71,91, while Mechanics was the lowest one, with the average score 64,08. Based on the results obtained, it can be inferred that the students are able to write a paragraph and their level of ability is in “good” level with the average score 66,98. By looking to the aspect the students mostly weak, that is Mechanics, this study recommended the students to do the two important ways that probably can solve this problem. The students need to learn and practice more about Mechanics. The more students learn and practice, the more they know about Mechanics. It will make them better in Mechanics aspect.Key Words: Study, Ability, Writing, Paragraph